2005
DOI: 10.1029/2004jd005487
|View full text |Cite
|
Sign up to set email alerts
|

Climatic response to high‐latitude volcanic eruptions

Abstract: [1] Strong volcanic eruptions can inject large amounts of SO 2 into the lower stratosphere, which over time, are converted into sulfate aerosols and have the potential to impact climate. Aerosols from tropical volcanic eruptions like the 1991 Mount Pinatubo eruption spread over the entire globe, whereas high-latitude eruptions typically have aerosols which remain in the hemisphere in which they where injected. This causes their largest radiative forcing to be extratropical, and the climate response should be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
188
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(200 citation statements)
references
References 32 publications
(50 reference statements)
12
188
0
Order By: Relevance
“…The forcing from volcanic eruptions tends to cool the tropics but produces some continental warming in the winter, similar in spatial pattern to a shift towards the positive phase of the Arctic Oscillation in the Northern Hemisphere (Stenchikov et al, 2006;Oman et al, 2005;Shindell et al, 2004). It has also been observed in the paleoclimate record that a multi-year, El Niño-like response can be induced in the atmosphere-ocean system as a response to explosive tropical volcanic eruptions (Adams et al, 2003).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The forcing from volcanic eruptions tends to cool the tropics but produces some continental warming in the winter, similar in spatial pattern to a shift towards the positive phase of the Arctic Oscillation in the Northern Hemisphere (Stenchikov et al, 2006;Oman et al, 2005;Shindell et al, 2004). It has also been observed in the paleoclimate record that a multi-year, El Niño-like response can be induced in the atmosphere-ocean system as a response to explosive tropical volcanic eruptions (Adams et al, 2003).…”
Section: Introductionmentioning
confidence: 80%
“…This response is due to the eruptions' injection of large amounts of sulfate aerosols into the stratosphere, which increases the amount of incoming solar radiation reflected back out to space at the top of the atmosphere. Although stratospheric aerosols tend to mix relatively quickly in the atmosphere (less than a few months), tropical eruptions tend to have greater climate impacts than high-latitude ones, due to both longer residence times of their aerosols as well as an apparent stronger dynamic response (Oman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The processes leading to El Niño-like anomalies in response to high-latitude eruptions are thus very different from those hypothesized to act in response to tropical eruptions (25,26) and rely on better-understood mechanisms (19,20). Only a few modeling studies (27)(28)(29)(30) have investigated the climate impacts of high-latitude volcanic eruptions, and none has looked at a potential influence on ENSO. Oman et al (29), using an atmospheric model coupled to a mixed-layer ocean, found a weakening of the summer monsoon circulation and precipitation over Africa and Asia in the summer of the eruption, consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The shifting of ITCZ has been discussed in not only Arctic geoengineering studies, but also in various other studies that investigate the effects of extra-tropical forcing such as high latitude sea ice cover changes (Chiang and Bitz 2005), high latitude volcanic eruptions (Oman et al 2005;Robock et al 2008;Haywood et al 2013), boreal deforestation (Devaraju et al 2015), high latitude ice sheets corresponding to the glacial periods (Broccoli et al 2006) and hemispherical asymmetries in clear-sky albedo (Voigt et al 2014). One of the effects associated with ITCZ shift is the change in cross-equatorial heat transport Frierson and Hwang 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A larger warming, relative to the scenario without geoengineering, was simulated in Northern India and Africa during summer due to weakening of monsoon circulation and reduction in cloud cover. The weaker monsoon circulation is due to a reduced temperature gradient between Indian Ocean and Asia (Oman et al 2005;Graf et al 1992), resulting in a large reduction in summer monsoon precipitation, for India, China, Sahel and Japan. Haywood et al (2013) simulated reduced precipitation in Sahel when geoengineering is implemented in the northern hemisphere (NH).…”
Section: Introductionmentioning
confidence: 99%